2005
DOI: 10.1242/jeb.01616
|View full text |Cite
|
Sign up to set email alerts
|

TheC. elegansT-type calcium channel CCA-1 boosts neuromuscular transmission

Abstract: SUMMARY Low threshold-activated or T-type calcium channels are postulated to mediate a variety of bursting and rhythmic electrical firing events. However,T-type channels' exact physiological contributions have been difficult to assess because of their incompletely defined pharmacology and the difficulty in isolating T-type currents from more robust high threshold calcium currents. A current in C. elegans pharyngeal muscle displays the kinetic features of a T-type calcium channel and is absent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 45 publications
6
82
0
Order By: Relevance
“…In the pharyngeal muscle, CCA-1 mediates a large inward depolarizing current, which is the first demonstrated role of the T-type calcium channel in C. elegans. This finding, along with the accompanying work (Steger et al, 2005), suggest that CCA-1 activates in response to excitatory inputs from the MC neuron and accelerates the action potential upstroke.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…In the pharyngeal muscle, CCA-1 mediates a large inward depolarizing current, which is the first demonstrated role of the T-type calcium channel in C. elegans. This finding, along with the accompanying work (Steger et al, 2005), suggest that CCA-1 activates in response to excitatory inputs from the MC neuron and accelerates the action potential upstroke.…”
mentioning
confidence: 58%
“…NGMSR is nematode growth medium (NGM; Sulston and Hodgkin, 1988) containing nystatin and streptomycin to prevent contamination . The wild-type Caenorhabditis elegans (Maupas, 1900) strain was Bristol (N2); mutant strains were: DA1651 cca-1(ad1650) X (Steger et al, 2005 IV (Trent et al, 1983), DA1426 exp-2(sa26 ad1426) V DA1694 egl-19(n582) IV; cca-1(ad1650) X.…”
Section: Worm Culture and Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…K.A. Steger and colleagues obtained the value about -73 mV 17 . Other studies 12,18 reported the values from -40 to -50 mV.…”
Section: Pharyngeal Muscle Cell Membrane Resting Potentialmentioning
confidence: 96%
“…The latter is activated by small depolarizations from resting potential, lifts membrane potential until EGL-19 can be activated and inactivates quickly 17 . The duration of APs in a body wall muscle and in a pharyngeal muscle is about 20 ms and 150 ms correspondingly 7,11 , which is much longer than in vertebrate skeletal muscle (<2 ms).…”
Section: Ion Channelsmentioning
confidence: 99%